Multi-hazard systems approach to overcome multi-hazard disaster in the northern coastal region of central jawa province - Muktiali Mohammad; Hadi Sudharto P.; Purnaweni Hartuti (E3S Web of Conferences)
Central Java Province is a region that has a high level of multiple disaster hazards. There are 21 types of natural disasters in the high category, such as floods, flash floods, extreme weather, extreme waves and abrasion, earthquakes, drought, several volcanic eruptions, liquefaction, tsunamis and landslides. A multi-system approach (through various adaptation & mitigation patterns based on multi-social-ecological systems) can increase community resilience. This research examine a multi-hazard system approach in increasing the resilience of coastal communities in the North Coast of Central Jawa (City of Pekalongan & Semarang). The research approach was carried out using a quantitative methods (scoring methods). Our study provides that structural mitigation (building sea dams and pumping programs), and adaptation (raising the height of house buildings & collaboration) was able to reduce the risk and increase community resilience to multi-disasters, especially floods, flash floods, tidal floods, and abrasion in Semarang and Pekalongan City. Our research suggests that it is important for policymakers to undertake structural mitigation through physical development of infrastructure and use of technology to reduce risk and increase community resilience. For communities, it is necessary to adapt by developing more disaster-resistant housing buildings.